Psychological Characteristics in Acute Mild Traumatic Brain Injury: An MMPI-2 Study. Issue 2 (4th March 2017) - Gass, Carlton S.; Rogers, David; Kinne, Erica
ABSTRACT: The psychological characteristics of acute traumatic brain injury (TBI) have received limited research focus, despite empirical evidence of their relevance for subsequent psychological adjustment and early therapeutic intervention. This study addressed a wide range of psychological features in 47 individuals who were hospitalized as a result of acute mild TBI (mTBI). Participants were screened from amongst consecutive TBI admissions for moderate to severe brain injury, and for pre-injury neurological, psychiatric, or substance abuse histories. Clinical and content scale scores on the MMPI-2 were explored in relation to patient gender, age, level of education, and extent of cognitive complaints. The results revealed diverse psychosocial problem areas across the sample, the most common of which were somatic and cognitive complaints, compromised insight, and a naively optimistic self-perception. The mediating roles of injury severity and demographic variables are discussed. Clinical implications and specific recommendations are presented.